Entrepreneurial potential of the agri-food sector: a systematic review of the literature - Mata Montenegro, Andrey (2024)
The present research carries out a systematic review of the literature on potential entrepreneurship within the context of agribusiness and is based on the review of scientific articles published in journals indexed in the Scopus database with the general objective of defining the state of the art of entrepreneurship in the agri-food sector with emphasis on its entrepreneurial potential. The review shows that intentional models of entrepreneurial behavior continue to be a predominant framework for understanding agricultural entrepreneurship. However, despite the importance of the agro-industrial sector for its ability to increase food access in the regions, the analysis shows that scientific research is scarce. This represents an opportunity for future research, especially when the theoretical underpinnings of planned behavior models suggest that their application should be specific in terms of object and context, in this case, business intentions are the object and the agribusiness sector, the context.